The Acoustic System of the Fendouzhe HOV - Yeyao Liu (MDPI AG, 2021)
Due to the strong absorption and attenuation of electromagnetic waves by water, radio communications and global positioning systems are lacking in the deep-sea environment. Therefore, underwater long-distance communications, positioning, detection and other functions depend on acoustic technology. In order to realize the above functions, the acoustic system of the Fendouzhe human occupied vehicle (HOV) is composed of eight kinds of sonars and sensors, which is one of the core systems of manned submersible. Based on the Jiaolong/Shenhai Yongshi HOVs, the acoustic system of the Fendouzhe HOV has been developed. Compared with the previous technology, there are many technical improvements and innovations: 10,000-m underwater acoustic communication, 10,000-m underwater acoustic positioning, multi-beam forward-looking imaging sonar, an integrated navigation system, etc. This study introduces the structure of the acoustic system of the Fendouzhe HOV and the technical improvements compared with the Jiaolong/Shenhai Yongshi HOVs. The results of the acoustic system are illustrated by the 10,000-m sea trails in the Mariana Trench from October to December 2020.